EVALUATION OF RADIATION FIELD VERIFICATION IN BREAST CANCER USING INTENSITY MODULATED RADIOTHERAPY TECHNIQUE ON DIFFERENT FRACTIONS - Nursama Heru; Abraham Panjaitan (Jurnal Penelitian Saintek, 2017)
This study was aimed at evaluating radiation field verification in breast cancer using Intensity Modulated Radiotherapy Technique (IMRT) on different fractions. The implementation of IMRT required 3 Dimensional verification processes to ensure the accuracy of the coordinates of the center caused by the shift. To analyze the value of the shift between Treatment Planning and Radiation Treatment, this research was conducted at the Department of Radiotherapy of Siloam TB Simatupang Hospital in February - June of 2017. The design of this study was quantitative descriptive by using 15 samples of breast cancer patients. The data were observed in the form of couch coordinate values X, Y, Z. The verification results using Cone Beam Computed Tomography (CBCT) then were analyzed using statistical test of Non Parametric Wilcoxon Test. The research instruments used were LINAC Varian Trilogy and verification tools On Board Imager CBCT. The result shows that longitudinal couch (coordinate Y) indicated significant differences from the Treatment Planning using Radiation Treatment. While on the lateral couch (X coordinates) and Vertical (coordinate Z) has no significant difference. From the study result, the average value of the verification has exceeded the tolerance standard at coordinate Y with value 0.2cm.